The perspective of social work education development in Malaysia and Australia - Mohamad, Mohd Suhaimi; Sarnon @ Kusenin, Norulhuda; Zakaria, Ezarina (Human Resource Management Academic Research Society, 2021)
This article explored the development of social work education in Malaysia and Australia focusing on three areas; professions, standards and education. The findings indicated that social work programmes and courses should be more entrepreneurial, research-oriented, and more efficient in its teaching methodology. Additionally, social work programmes should emphasise on the development of social work as a profession, strengthen the governance of social work education, and develop programs that focus on the global agenda. In Malaysia, the social work education began in 1975 whereas in Australia, it started in 1940 with the launch of Social Work Degree Program in the University of Sydney. In Australia, social work programmes are accredited by a professional body known as the Australian Association for Social Work (AASW), while in Malaysia, there is no established or authorised professional body to accredit the programmes. Without it, the path for social work profession to develop may be affected or compromised. This could be the contributing factor causing the delay in the development of social work education in Malaysia when compared to Australia.